Two more new species of armoured scale insect (Hemiptera: Sternorrhyncha: Coccoidea: Diaspididae) from Fiji - Łagowska, Bozena; Hodgson, Chris (Zootaxa, 2012)
The adult females of two new species of Diaspididae (Hemiptera: Coccoidea) are described and placed in Anzaspis Henderson(previously only known from New Zealand): A. neocordylinidis Łagowska & Hodgson and A. pandani Łagowska & Hodgson.The former is close to A. cordylinidis (Maskell), currently only known from New Zealand and found on the same host plantspecies, and the latter is very close to Chionaspis pandanicola Williams & Watson, only currently known from Fiji, and alsocollected on the same host plant species. Two previously described Chionaspis species already known from Fiji, i.e. C.freycinetiae Williams & Watson and C. pandanicola Williams & Watson are transferred to Anzaspis as Anzaspis freycinetiae(Williams & Watson) comb. nov. and A. pandanicola (Williams & Watson) comb. nov., and a third species, C. rhaphidophoraeWilliams & Watson, is transferred to Serenaspis as Serenaspis rhaphidophorae (Williams & Watson) comb. nov.. The reasonsfor these nomenclatural decisions and the relationship between the scale insect fauna of Fiji and New Zealand are discussed. A key is provided to all related species in the tropical South Pacific and New Zealand.